Assessment of College Entrepreneurship and Innovation Education Effect for Sci-Tech Service Industry - Yongzhi Chang; Yuan Liu (Discrete Dynamics in Nature and Society)
Based on the analysis of the importance and necessity of evaluating the college entrepreneurship and innovation (E&I) education effect for the sci-tech service (STS) industry, from four aspects of top-layer design, college environment, faculty and learner assessment, an assessment index system for the effect of college E&I education is constructed. Through analytic hierarchy process (AHP), this paper also makes a comprehensive and objective assessment and analysis on the effect of college E&I education, which is oriented to the STS industry. Among the primary layer indicators, the weight coefficient of learner assessment is 0.4444, followed by the faculty, and the weight coefficient is 0.3061. Additionally, this proves that lecturers and learners are the focus and primary body of E&I education activities in colleges for STS industry. The theoretical concept and practical ability of learners is the most important index to test the assessment of E&I education effect. Lecturers’ teaching methods and their own experience are important for the effect assessment of E&I education, and the environment of E&I education is important for the effect assessment of education. The construction of innovative and entrepreneurial lecturers is critical to education effect assessment.